Structural and optical study of Zn-doped As2Se3 thin films: Evidence for photoinduced formation of ZnSe nanocrystallites; AIP Advances; Vol. 9, iss. 6 - Azhniuk Yu. M.; Solonenko D. I. Dmytro; Sheremet E. S. Evgeniya Sergeevna; Dzhagan V. Volodymyr; Loya V. Yu. Vasyl; Grytsyshche I. V. Iaroslav; Schulze S. Steffen; Hietschold M. Michael; Gomonnai A. V. Alexander; Zahn D. R. T. Dietrich (2019, 2019)
Title screen